Psychological causes of non-compliance with electronically monitored occlusion therapy for amblyopia. Issue 11 (5th August 2009) - Loudon, S E; Passchier, J; Chaker, L; de Vos, S; Fronius, M; Harrad, R A; Looman, C W N; Simonsz, B; Simonsz, H J
Abstract : Aim: To analyse psychological causes for low compliance with occlusion therapy for amblyopia. Method: In a randomised trial, the effect of an educational programme on electronically measured compliance had been assessed. 149 families who participated in this trial completed a questionnaire based on the Protection Motivation Theory after 8 months of treatment. Families with compliance less than 20% of prescribed occlusion hours were interviewed to better understand their cause for non-compliance. Results: Poor compliance was most strongly associated with a high degree of distress (p<0.001), followed by low perception of vulnerability (p = 0.014), increased stigma (p = 0.017) and logistical problems with treatment (p = 0.044). Of 44 families with electronically measured compliance less than 20%, 28 could be interviewed. The interviews confirmed that lack of knowledge, distress and logistical problems resulted in non-compliance. Conclusion: Poor parental knowledge, distress and difficulties implementing treatment seemed to be associated with non-compliance. For the same domains, the scores were more favourable for families who had received the educational programme than for those who had not.